Forced ecosystems and digital stepchildren: reconfiguring advertising suppliers to realize disruptive social media technology - Ozcan, P; Hannah, D (Institute for Operations Research and Management Sciences (INFORMS), 2020)
Research often examines disruption in the context of head-to-head competition between firms and technologies. In contrast, we examine the unique dynamics of disruptive technologies within supplier ecosystems. We do so through an inductive multiple case study set in the global advertising industry from 2008–2013, as the industry grappled with the emergence of social media. Using rich archival and field data, we closely track five global consumer goods manufacturers and their associated advertising suppliers as they attempted to integrate social media into their advertising activities. Our primary contribution is to unpack the process by which firms reconfigure their supplier ecosystems to address disruptive new technologies. Our framework reveals that integrating new technologies may require firms to reconfigure the distributions of both activity and power, and that fundamental trade-offs may leave the value of new technologies unrealized. Broadly, we contribute to research and theory on buyer-supplier relationships, alliances, and technology disruption by bringing a more realistic perspective that considers firms’ network of suppliers and interfirm turf wars in technology adoption.